Strategic Planning of Surabaya City Government in Managing Public Green Open Space (A Study at the Surabaya City Sanitation and Green Open Space Agency) - Oktarizka Reviandani; Soesilo Zauhar; Endah Setyowati (Postgraduate School Universitas Brawijaya, 2020)
Public Green Open Space is one of the important components in managing cities in order to realize the mandate of Law Number 26 of 2007 concerning Spatial Planning, namely the proportion of Public Green Open Space in city areas of at least 20% of the total area. This study aims to describe and analyze the Strategic Planning of the Sanitation and Green Open Space Agency in the Management of Public Green Open Space in Surabaya City as well as the Supporting and Inhibiting Factors in the Management of Public Green Open Space. This study applied a descriptive study method with a qualitative approach and the interactive model of qualitative data analysis. The findings indicate that the management of public green open space is guided by the Strategic Plan of the Sanitation and Green Open Space Agency through the Green Open Space Management Program, namely the Arrangement of Green Open Space, Maintenance and Procurement of Park and Green Belt Facilities, and Maintenance and Procurement of Recreational Park Facilities and Infrastructure. The supporting factor in public green open space management is the existence of an institution or organization involved, green open space management program, human resources, community participation, and cooperation with the private sector. Meanwhile, the limited funds for implementing public green open space management program activities and land ownership status are the inhibiting factors in the management of public green open spaces in Surabaya.